Efecto del tamaño de esqueje en la proliferación de plantas de yuca (Manihot esculenta Crantz) en cámara térmica - Cedeño Cedeño, Nathaly Victoria (2025)
The main objective of this research was to evaluate the effect of cutting size on the proliferation of cassava plants in a thermal chamber in the plant variety P-652 “La rendidora”. A Completely Random Design (DCA) was used with an AxB arrangement, with factor A being the propagation environments: thermal chamber (A1), flower bed (A2) and factor B being the size of cuttings: 2 internodes (B1), 4 internodes (B2), 6 internodes (B3), 8 internodes (B4) and 10 internodes (B5). Statistical analysis was performed using Infostat software, using the Tukey test at 0.05% significance. The size of cuttings B4 and B5 reached the highest means in the interactions of A1B5 and A2B5. The 99% taking of the cuttings was reflected in A1B5; A1B4; A2B5 and A2B4. The highest numbers of shoots 3.55 and 3.22 were reached by cutting sizes B4 and B5 at 45 days, respectively. The highest multiplication rate 0.11 was recorded by B5 and the A2B5 interaction. It is concluded that cuttings with 8 internodes proliferate optimally in thermal chambers. The multiplication rate in the flowerbed is higher than in the thermal chamber, with cuttings greater than 8 internodes. The quality of seedlings is related to the size of cuttings from six internodes, regardless of the propagation environment.